Survival in Cases of Intestinal Tumors - Santos,Maurício Daniel dos (2021)
Abstract Objective To assess the survival rate of patients with colorectal cancer at Hospital Universitário Alzira Vellano, in the municipality of Alfenas, state of Minas Gerais (MG), Brazil, from 2007 to 2016. Methodology A search was conducted in the laboratory files and medical records of patients diagnosed with colorectal cancer and cared for during the aforementioned period. Results In total, 128 cases were found: 52.3% were men, and 47.7% were women, with ages ranging from 25 to 91 years. The most common types of cancer in both genders were of the colon, rectum and sigmoid. The most common stages were T3N1Mx, followed by T3N0Mx and T3N2Mx. Patients with T1 or T2 cancers had a 100% survival rate, whereas the rate for those with grade 4 (T4) was of 0%. An association (p<0.05) of the location of the tumor with the survival rate was confirmed. Conclusion There was a high mortality rate among patients diagnosed with colorectal cancer at Hospital Universitário Alzira Vellano from 2007 to 2016.